WHO’s pandemic response recommendations after COVID-19: lessons learned or learnings lost? - von Agris, Jean Merlin; Bell, David; Tacheva, Blagovesta; Brown, Garrett Wallace (Frontiers in Public Health, 2025)
ObjectivesThis article examines how the World Health Organization’s (WHO) recommendations and guidelines on public health and social measures (PHSM) have changed since COVID-19. Doing so allows insights on what lessons WHO has learned from the COVID-19 response.MethodsThe article analyses six recent WHO publications detailing recommendations on PHSM and compares them against three pre-COVID-19 WHO documents. The analysis also assesses the evidence-base used for these recommendations to better understand WHO’s substantive basis and rationale for the PHSM changes.ResultsThe analysis reveals substantial changes in WHO recommendations, often without systematic evidence assessment. Several population-wide interventions including quarantine, travel measures, and universal masking have become normalized in post-COVID documents, despite being previously discouraged. When evidence is cited, it often pertains to narrowly defined short-term outcomes, with limited consideration of broader societal impacts. Adverse effects of PHSM are recognized, but mitigation takes priority over avoiding harms.ConclusionSystematic evaluation of the evidence on PHSM during the COVID-19 pandemic, including their effectiveness and collateral effects, is imperative before revising changes in recommendations for future pandemics.